Identifying Nonphysical Intimate Partner Violence in Relationships: The Role of Beliefs and Schemas - Minto, Kiara (Journal of interpersonal violence, 2022)
While substantial research has been conducted on intimate partner violence (IPV), comparatively little research has examined peoples’ perceptions of which behaviors comprise this form of abuse. Early identification of IPV is critical to ending abuse, however, forms of IPV that typically occur earlier in a relationship (e.g., nonphysical abuse) may not be core components of peoples’ mental frameworks (schemas) of IPV and may therefore be less commonly identified as abusive. To explore this, in Study 1 participants from an Australian University (N = 86) separately described the relationships with IPV and nonphysical IPV. Analyses identified control, power imbalance, stereotypical gender dynamics (male perpetrator, female victim), physical abuse, and having a low socioeconomic status abuser as common components of participants’ IPV schema when not prompted with type of abuse. However, participants largely failed to describe nonphysical IPV behaviors, suggesting limited awareness of the specific behaviors that constitute abuse. To explore this in Study 2, participants from an Australian University (N = 305) were asked to categorize a range of specific behaviors (including physically abusive, nonphysically abusive, and nonabusive behaviors) as definitely, maybe, or never abusive. Drawing on the known positive association between gender and romantic beliefs with the experience of abuse, we also assessed the relationship of identification of IPV behaviors to these beliefs. Moderated multilevel modeling showed that nonphysical IPV behaviors were generally perceived as less abusive than physical IPV behaviors. In addition, stronger endorsement of romantic jealousy was associated with evaluating nonphysical IPV as less abusive. However, romantic jealousy beliefs were not significantly associated with the perceived abusiveness of physical IPV behaviors. Findings support the conclusion that individuals’ IPV schemas contribute to a failure to identify nonphysical IPV behaviors as abusive, and this is particularly true for people who more strongly endorse romantic jealousy.